Empowering the future: improving community wellbeing and health literacy through outreach and service-learning - Restini, Carolina B. A.; Weiler, Tracey; Porter-Stransky, Kirsten A.; Vollbrecht, Peter J.; Wisco, Jonathan J. (Frontiers in Public Health, 2024)
Institutions training future healthcare professionals in healthcare and community engagement play a crucial role beyond traditional classroom settings. Recognizing their potential to support under-represented groups and minorities, institutions increasingly encourage engagement with schools and community organizations. However, work remains to advance meaningful and impactful educational outreach and service-learning programs. This manuscript synthesizes the perspectives of a group of medical school educators to discuss developing sustainable programs to engage youth in Science, Technology, Engineering, Math, and Medicine (STEMM) education with a focus on biomedical science. Through near-peer education and service-learning, healthcare students can impart knowledge, provide mentorship, promote enthusiasm for STEMM fields, and nurture health-related self-efficacy within individuals and communities. Collaborative efforts through student-as-teacher approaches bridge health-related disparities and cultivate healthier, more empowered futures for all. We advocate for community outreach strategies that target future health professionals early in their education and support the scholarship of teaching and learning and program evaluation. Successful long-term programs must ensure that results are systematically assessed, measured, and perpetuated. This perspective aims to highlight the role of service learning and community outreach in increasing individual health literacy and fostering an enduring interest in STEMM careers, thereby empowering the next generation of elementary and secondary school students.